The long- and short-run impact of oil price changes on major global economies - Thomas Heidorn; Sophie Van Huellen; C. Ruehl; F. Woebbeking (Frankfurt School of Finance & Management, 2017)
In the context of the recent slump in global oil prices, the paper investigates the effect of oil price shocks on the economic performance of 51 individual OECD and OPEC economies. We propose an error correction model which allows us to differentiate between short- and longrun price effects. For robustness, structural breaks and potential asymmetries are incorporated. Our approach is particularly interesting, since economic performance is not only measured by GDP, but also by equity indices from the MSCI family. The equity indices provide valuable insights into financial transmission mechanisms, in addition to macroeconomic channels, at much higher frequency than conventional GDP data. We are able to present robust estimates for the severity of oil price shocks for individual economies and thereby identify winners and losers under the current oil price regime.
Keywords: C32; E31; F43; Q32; Q43; 330